Analysis of Financial Performance Based on Financial Analysis Ratio, Common Size and Trend in Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Period 2019-2021 - Rahmatulloh, Villa Susanti; Sasanti, Elin Erlina; Hudaya, Robith (Jurnal Manajemen (Edisi Elektronik), 2023)
This study analyzes the financial performance in Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan period 2019-2021.This study using analysis of financial ratios, which include liquidity ratio, solvency ratio, profitability ratio, activity ratio, common size analysis, and trend analysis. This study also analyzes forecasting in ratio analysis for the period 2022-2024 in BPJS Kesehatan. The purpose of this study are to provide a systematic overview description of the state of the financial performance on BPJS Kesehatan and this kind of research is a case study using quantitative method. The type of quantitative data obtained from the website bpjs-kesehatan.go.id. The result of this study are: financial analysis ratio shows an increase in the liquidity ratio, solvency ratio, and profitability ratio, but there are fluctuations in the activity. The common size analysis shows fluctuations in the financial position and income statements that increase sably and decrease indignificantly. Trend analysis has good results on the statements of financial position and income statements. In the BPJS Kesehatan forecasting analysis shows increase results for the next three years and there is no deficit because it shows positive results in each ratio. Keywords: ratio analysis, common size, trend, forecasting